2011
DOI: 10.1017/s0950268811002056
|View full text |Cite
|
Sign up to set email alerts
|

Detection of West Nile virus genome and specific antibodies in Iranian encephalitis patients

Abstract: West Nile virus (WNV) is a mosquito-borne flavivirus which circulates in birds, horses and humans. An estimated 80% of WNV infections are asymptomatic. Fewer than 1% of infected persons develop neuroinvasive disease, which typically presents as encephalitis, meningitis, or acute flaccid paralysis. This study was conducted from January 2008 to June 2009 in Isfahan, Iran. Patients attending the emergency department with fever and loss of consciousness were consecutively included. Cerebrospinal fluids (CSF) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Test samples and peroxidase-labeled anti-human or anti-animal immunoglobulin were added. After incubation for 10 min, optical densities were read ( 6 ). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Test samples and peroxidase-labeled anti-human or anti-animal immunoglobulin were added. After incubation for 10 min, optical densities were read ( 6 ). …”
mentioning
confidence: 99%
“…A reverse transcription PCR was conducted by using a One-Step RT-PCR Kit (QIAGEN). Samples were subjected to 1 cycle at 50°C for 30 min to synthesize cDNA; 95°C for 15 min; and 95°C for 30 s, 54°C for 30 s, and 72°C for 60 s; and a final extension at 72°C for 5 min ( 6 ). The serum sample was positive for IgG against WNV.…”
mentioning
confidence: 99%
“…Although, 75% of infected human cases had animal contacts, these data did not suggest that human infections These data are complementary with the circulation of WNV among the population in Isfahan Province, since our previous study on encephalitis patients in Isfahan Province showed that 1.2% of them were positive for both serum and CSF RT-PCR, and 2.4% were positive only for IgG antibody (Chinikar et al 2012).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, a more recent study on healthy human blood donors in 2005 showed that 5% of donors were IgG positive to WNV (Talebian 2010). In our previous study between 2008 and 2009, we demonstrated that 3.6% of patients with encephalitis symptoms had been infected by WNV (Chinikar et al 2012).…”
Section: Introductionmentioning
confidence: 90%
“…Regionally, several reports from the Middle East have shown that the seroprevalence of WNV ranged from 1·3% to 26% of the populations [24][25][26][27][28][29][30][31]. However, an outbreak of WNV neuroinvasive disease has been reported only in Israel.…”
Section: Introductionmentioning
confidence: 99%